Human Capital of Transnational Corporations in the Energy Sector - Bogomolova, Yuliya I.; Belokurova, Elena V.; Meshkov, Vladimir R.; Pavlov, Evgeniy O. (International Journal of Energy Economics and Policy, 2018)
For the development of the energy sector, at the present stage, it is necessary to use certain resources. The paper analyzed the application of human capital in the energy sector. To achieve this goal, the authors used the method of offset. It is established that the world energy consumption increases, and the dynamics of the employed population in the energy sector remains within the same norm. It is determined that an important factor for the development of the economy is the gross regional product. As its increase helps to reduce energy intensity. The authors show that human potential is not only a personal characteristic received by the employee independently, but also by the acquired position, which is ensured by the implementation of corporate tools. The paper considers the economic, social and legal provision of such instruments. Keywords: labor resources, electrification, energy efficiency, expert evaluation, energy system. JEL Classifications: A10, P48 DOI: https://doi.org/10.32479/ijeep.6901